EVALUASI PROGRAM PEMBELAJARAN IPS DI SDN SE-WILAYAH IV KECAMATAN DONRI DONRI KABUPATEN SOPPENG - Salmawati, Salmawati (Universitas Negeri Makassar, 2017)
This research aims at describing IPS (Social Science) learning program at SDN Regional IV in Donri-Donri subdistrict of Soppeng district based on the aspects of context, input, process, and product. This research is evaluation research which uses CIPP model (Context, Input, Process and Product). The subjects of the research were teacher and students at SDN Regional IV in Donri-Donri subdistrict in Soppeng district. Data was collected by using quessionaries, observation, and document analysis. Data was analyzed quantitatively by conducting data collection, data reduction, data presentation, and conclution. This result of the research reveals that IPS Program planning is in poor category, social learning fasilities is in exelent category, teacher’ performances and class condition in IPS learning process is already in exelent category, and OPS learning outcomes at SDN regional IV in Donri-Donri subdistrict of Soppeng district is in good category.